Web-based Blood Donor Management Information Sytem using Waterfall Method - Andriani, Reza Silvia; Irmayani, Deci; Ritonga, Ali Akbar (Sinkron : jurnal dan penelitian teknik informatika, 2022)
PMI Labuhanbatu Regency is one of the central PMI branches where there is a division that handles the blood donation process, namely the Blood Transfusion Unit. UTD PMI Labuhanbatu Regency has the duty to serve blood donation activities and provide blood stock for the Labuhanbatu community in need. As a unit that provides blood donors, UTD PMI Labuhanbatu must always be ready to provide the services needed. One of the concerns is the issue of blood stock availability. If there are many people who need blood, then UTD must be ready to serve. If the amount of blood stock is reduced, then people will find it difficult to get blood. For this reason, the issue of blood availability must always be the main concern of UTD PMI Labuhanbatu. This study aims to build a blood donor information system at the PMI Blood Transfusion Unit in Labuhanbatu Regency. The system built applies a web-based framework. The system development applies the Waterall method which includes the process of needs analysis, design, implementation, testing, and maintenance. After designing, implementing and testing, the results obtained are the system has been successfully developed and all designs are in accordance with what is implemented. The conclusion from this research is that the blood donor information system that has been developed at UTD PMI Labuhanbatu Regency has been able to provide convenience for admins and users in managing donor and blood stock management.